Toward mobility-based surveillance model for static multi-targets - Hameed, Shihab A. (Institute of Research and Journals, 2015)
Several individuals or families nowadays own more than one property. It could be fixed properties like houses and offices or moving properties like cars or other automobiles. Generally the crime cases involving home intrusion and car theft have been rising, resulting in many cases reported daily about such crimes. People become more aware on safety of their properties and start to subscribe to some security systems such as CCTV, ADT, and car alarm. Even so, the number of such crime cases is not much reducing, rather elevates, as criminals today become more professional and know how to disable security systems from working. To overcome such limitations, an efficient security system is needed that integrate different technologies to detect the presence of an intruder. In this paper, a new Mobility Based surveillance model for Static Multi-Targets MBSMT is proposed to offers a suitable alarm system for owners of multi-properties (targets). The model integrates latest or suitable technologies in mobility, micro-controller, sensors, camera and GPS to produce a low cost product. This paper focused only on static properties and shows the design and implementation of the proposed MBMTS Model. Sample of implementation results are obtained.